Bioart. Issue 12 (December 2015) - Yetisen, Ali K.; Davis, Joe; Coskun, Ahmet F.; Church, George M.; Yun, Seok Hyun
Abstract : Bioart is a creative practice that adapts scientific methods and draws inspiration from the philosophical, societal, and environmental implications of recombinant genetics, molecular biology, and biotechnology. Some bioartists foster interdisciplinary relationships that blur distinctions between art and science. Others emphasize critical responses to emerging trends in the life sciences. Since bioart can be combined with realistic views of scientific developments, it may help inform the public about science. Artistic responses to biotechnology also integrate cultural commentary resembling political activism. Art is not only about 'responses', however. Bioart can also initiate new science and engineering concepts, foster openness to collaboration and increasing scientific literacy, and help to form the basis of artists' future relationships with the communities of biology and the life sciences. Trends: Bioart is a contemporary art form that adapts scientific methods and biotechnology to explore living systems as artistic subjects. Interdisciplinary bioart initiatives blur boundaries between art and modern biology with an emphasis on philosophical, societal, and environmental issues. Bioart plays an important role in critically challenging emerging life science applications, stimulating of scientific thinking, and contributing to new research questions and new technologies. New concepts emerge for bioart in physical, digital, and computational forms. Bioart receives ethical criticism for modifying living systems.